A multi-methodological analysis of Jabuticaba's supply chain in an agricultural cooperative production - Natallya de Almeida Levino; Madson Monte; Carlos Costa; Walter Lima Filho (Logistics, 2022)
Background: In the late 1990s, the idea of fighting drought gave way to the concept of how to live with drought in the Brazilian semi-arid region. From this perspective, the Brazilian Federal Government's investment in social technology and education encouraged local agricultural production and subsistence agriculture began to have a surplus for commercialization and income generation. However, there are still difficulties in the development of the productive chain, as perceived in Alagoas, Brazil, with the jabuticaba fruit and its derivatives. In this locus, problems related to the creation of value and distributions of the product were identified. Methods: This study proposed a participant observation in a rural producers' association and a multimethodological approach based on VFT (Value-Focused Thinking) and SWOT analysis aiming to structure the problem, identify communities' objectives and develop alternatives to solve these problems so that they can get more out of their production. Results: showed that the product has marketing potential due to its differential, but the producers are limited in the process of distributing the goods. Conclusions: So, this study was able to analyze the problems of this productive system in a structured way, generating suggestions for actions to achieve the strategic objectives of the cooperative.
Keywords: 650; family farming; multimethodology; structuring problem; supply chain